The Czech manuscripts : forgery, translation, and national myth - Cooper, David L., 1970- (Ithaca : Northern Illinois University Press, an imprint of Cornell University Press, 2023)
"A study of the nineteenth-century Czech forged manuscripts (Rukopis královédvorský and Rukopis zelenohorský) that examines the contexts of their creation and reception and their poetics"--
The phenomenon of the manuscripts -- Forgery as a romantic form of authorship : the manuscripts in comparative perspective -- Successful forgeries: oral traditional epic poetics in the Czech manuscripts -- Translation, pseudotranslation, and the manuscripts -- Faith, ritual, and the manuscripts.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 28, 2023).
JSTOR
Keywords: Hanka, Václav, -- 1791-1861.; Hanka, Václav, -- 1791-1861.; Rukopis Královédvorský (Hanka, Václav); Zelenohorský rukopis (Hanka, Václav); Czech literature -- 19th century; Literary forgeries and mystifications -- History -- 19th century; Nationalism and literature; Faux et supercheries littéraires -- Histoire -- 19e siècle.; Nationalisme et littérature.; LITERARY CRITICISM / Russian & Former Soviet Union; Czech literature; Literary forgeries and mystifications; Nationalism and literature; Museology & heritage studies; Antiques, Collecting; 1800-1899; Electronic books; Electronic books; History